The Climate Changes and Their Influences on the Agriculture Being Rendered by Product Management Method - VĂCĂRESCU HOBEANU, Loredana (Journal of Advanced Research in Management, 2020)
The climate changes, through their consequences and risks for society, the economy and the environment, are now aconcern for people everywhere. The people around the world are concerned about the global climate change they perceive as a threat through the consequences they have now or may have in the future. Mitigating the effects of the climate change on agriculture is a priority objective in the strategic development actions of the EU Member States. The interdisciplinary nature of the actions implies a global approach by identifying and correlating the activities of development and implementation of intra- and inter-sectoral measures with those of responding to the effects of the climate changes. The product management method allows all issues related to a homogeneous product or group of products to be assigned to a specific, separate management within that unit. The method is a great importance for the improvement of the management activity in the agricultural units, with the specification that it must be adapted to the specifics of the agricultural production and of the particularities of the agriculture.